Antiglycating effects of citrus flavonoids and associated mechanisms - Yunli Xiao; Junfeng Shen; Jianfeng Zhan; Limin Guo; Chi-Tang Ho; Shiming Li (Food Science and Human Wellness)
Glycation of proteins and DNA forms advanced glycation end products (AGEs) causing cell and tissue dysfunction and subsequent various chronic diseases, in particular, metabolic and age-related diseases. Targeted AGE inhibition includes scavengers of reactive carbonyl species (RCS) such as methylglyoxal (MG), glyoxalase-1 enhancers, Nrf2/ARE pathway activators, AGE/RAGE formation inhibitors and other antiglycatng agents. Citrus flavonoids have demonstrated antioxidant and anti-inflammatory effects and are also found to be effective antiglycating agents. Herein, we reviewed the up to date progress of the antiglycation effects of citrus flavonoids and associated mechanisms. Major citrus flavonoids, hesperedin and its aglycone, hesperetin, inhibited glycation by scavenging MG forming mono- or di-flavonoid adducts with MG, enhanced the activity of glyoxase-1, activated Akt/Nrf2 signal pathway while inhibiting AGE/RAGE/NF-κB pathway, reduced the formation of Nε-(carboxylmethyl)lysine (CML) and pentosidine, inhibited aldol reductase activity and decreased the levels of fructosamine. The antiglycating activity and mechanisms of other flavonoids was also summarized in this review. In conclusion, citrus flavonoids possess effective antiglycating activity via different mechanisms, yet there are many challenging questions remaining to be studied in the near future such as in vivo testing and human study of citrus flavonoids for efficacy, effectiveness and adverse effects of citrus flavonoids as a functional food in managing high levels of AGEs and controlling AGE-induced chronic diseases, diabetic complications in particular.